2022
DOI: 10.3390/plants11243472
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Mechanisms and Control Technologies of Chilling Injury and Fungal Diseases of Postharvest Loquat Fruit

Abstract: Loquat is a popular fruit widely cultivated all over the world. It is rich in minerals and carotenoids and has high commercial value. At room temperature, loquat fruit is impressionable to water and nutritional losses, physical damage, and microbial decay, resulting in a short postharvest life. Low-temperature storage is routinely used to prolong the shelf life of loquat fruit; however, cold storage can also lead to lignification of flesh tissue, which is one of the major symptoms of chilling injury (CI), redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…It has been shown that improved plant resilience is directly connected to the increasing levels of sulphur dioxide (SO 2 ) uptake and SO 2 metabolism in plants. The application of SO 2 helps to maintain the equilibrium between the production of ROS and their detoxification, which in turn helps to suppress ROS formation and prevent the lignification of the flesh of loquat fruit [ 33 ]. The treatment of loquat fruit with an SO 2 -releasing agent (SO 2 -releasing pad) substantially reduced the prevalence of decay and browning.…”
Section: Postharvest Handling and Storage Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that improved plant resilience is directly connected to the increasing levels of sulphur dioxide (SO 2 ) uptake and SO 2 metabolism in plants. The application of SO 2 helps to maintain the equilibrium between the production of ROS and their detoxification, which in turn helps to suppress ROS formation and prevent the lignification of the flesh of loquat fruit [ 33 ]. The treatment of loquat fruit with an SO 2 -releasing agent (SO 2 -releasing pad) substantially reduced the prevalence of decay and browning.…”
Section: Postharvest Handling and Storage Techniquesmentioning
confidence: 99%
“…Previously, the metabolic changes during fruit ripening and the postharvest quality management of loquat fruit have been summarized in different reviews [ 2 , 32 ]. Moreover, the mechanism and control strategies of major fungal diseases in loquat fruit have also been presented in a recent review [ 33 ]. However, comprehensive information explaining harvest maturity indices, harvest and handling at the farm, postharvest quality management techniques, postharvest disorders and their management, as well as major diseases in the loquat fruit were not discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The cell membrane is the primary location where chilling injury takes place. Phase changes under low temperature stress and a gradual transformation from liquid crystal to solid state, followed by increased permeability and damage to the cell membrane, have an impact on the structure and function of the membrane (Zhang et al, 2022c). Another significant contributor to cell membrane damage is membrane lipid peroxidation and decomposition, which is mostly manifested by decreased unsaturation of membrane phospholipids and fatty acids and elevated MDA levels.…”
Section: Major Diseases Of the Loquat Fruitmentioning
confidence: 99%
“…Loquat is a chilling‐sensitive fruit (Xu et al, 2019). When kept below 5°C, loquats are susceptible to cold damage, when kept above 0°C, they are susceptible to lignification, interior browning, and juicy loss (Dhiman et al, 2022; Wang et al, 2021; Zhang et al, 2022c). It is believed that chilling injury (CI), which results in the rotting of loquat fruit, is brought on by aberrant alterations in the cell wall (Dhiman et al, 2022).…”
Section: Major Diseases Of the Loquat Fruitmentioning
confidence: 99%
See 1 more Smart Citation